Factors Associated with Pneumonia among Children at Namang Primary Health Center - Lia Marluzianty; Indri Puji Lestari (Inspirasi Foundation, 2026)
Introduction: Pneumonia remains a major cause of morbidity and mortality among children worldwide, particularly in developing countries, and is strongly associated with preventable risk factors such as inadequate nutrition, incomplete immunization, and lack of exclusive breastfeeding. This study aims to analyze the relationship between exclusive breastfeeding, nutritional status, and immunization status with the incidence of pneumonia among children in the working area of Namang Community Health Center. Objective: This study aims to analyze the association between exclusive breastfeeding, nutritional status, and immunization status and the incidence of pneumonia among children in the working area of the Namang Community Health Center in 2025. Method: This study used a cross-sectional design with independent variables (exclusive breastfeeding, nutritional status, and immunization history) and dependent variable (pneumonia incidence in children). The population size in this study was 501 people, and a sample of 91 people was calculated using simple random sampling. Result: The results of the study using the Chi-Square statistical test obtained a p-value of 0.000 < 0.05 for the exclusive breastfeeding variable, 0.000 < 0.000 for nutritional status, and 0.000 < 0.05 for immunization history. This indicates a significant relationship between exclusive breastfeeding, nutritional status, and immunization history and the incidence of pneumonia in children in the Namang Community Health Center Work Area in 2025. Conclusion: The recommenddations in this study are expected to serve as a reference source and provide insights for nursing students during their field practice, so that they understand the factors that can influence the incidence of pneumonia in children.